Step by step trasvaginal ultrasound - Dastir, Kakoli (Japee Brothers Medical Publishers, 2015)
Primarily designed to make transvaginal ultrasound more easy and understandable to the junior doctors and students. - Includes schematic diagrams of al the ultrasonography plates to make it more interesting and needful in day-to-day practice. - Incorporates 19 chapters in all consisting of focusing pelvic organs; ultrasound anatomy of uterus, cervix and ovaries.